REBRANDING AIR MINUM DALAM KEMASAN AQUACUI - Welin Kusuma; Maya Luciawati (Jurnal Teknobisnis, 2006)
PT Aneka Tirta Sukoindo is a bottled spring water producer which uses "Aquacui" trademark. This company was established on IS t January, 2003 and is located in Sukorejo-Pandaan. Recently, PTAneka Tirta Sukoindo has been indicted by PT Aqua Golden Mississippi, a pioneer company and a market leader in bottled spring water industry. The reason of the indictment was the use of the word "Aqua" in "Aquacui" brand. PT Aqua Golden Mississippi claims that Aquacui has duplicated the Aqua brand name. Because of this indictment, PT Aneka Tirta Sukoindo needed to be rebranded the Aquacui. Rebranding is a process in redefining and positioning a brand strateu, which may have several forms. The forms can be a change of the name or a change in imagery (visual symbols and packaging designs). Rebranding of Aquacui was prompted by a crisis from PT Aqua Golden Mississippi's indictment and an improvement strategy of Aquacui's product image in the market place. The results of the Aquacui's rebranding process was redefinition of the brand name, brand core, brand positioning, brand personality, brand culture, brand architecture, brand visual identity and brand communication strateu.